Trends and prospects for livestock systems in the semi-arid tropics of sub-Saharan Africa - Williams, Timothy O.; Thornton, Philip K.; Fernández Rivera, S. (International Crops Research Institute for the Semi-Arid Tropics, 2002)
In semi-arid sub-Saharan Africa as in many dryland areas, livestock are an integral part of the farming systems. Livestock offer opportunities for risk coping, farm diversification and intensification and provide significant livelihood benefits to the poor. The ability of livestock systems to continue to provide these functions and services will depend on their future evolution pathways and Development priorities which can be determined through a careful analysis of the dynamics, opportunities and challenges confronting these systems. The purpose of this paper is to review the Development of livestock production systems in semi-arid tropics of sub-Saharan Africa. The paper examines the ways in which social, economic, institutional and technological factors have influenced the evolution of livestock systems and identifies promising research approaches, technologies, policy and institutional reforms that can improve systems performance and sustainability and contribute to poverty reduction.